The Biblical Hebrew verb: a linguistic introduction - Cook, John A. (Learning Biblical Hebrew, 2024)
A leading expert in Biblical Hebrew describes the Hebrew verbal system in a way that helps readers understand its grammar and provides linguistic tools for interpreting and translating the Hebrew Bible.